Family-School Partnerships in Improving Academic Performance of Grade 10 Learners in a Rural Public School - Maruatona, Rorisang; Maseko, Nonhlanhla Desiree (Central European Journal of Educational Research, 2025)
Family-school partnerships address academic difficulties and ensure the performance of learners, thus, they are crucial for the improvement of learners. However, these collaborative partnerships can occasionally be hampered by problems including inadequate communication, and limited parental involvement. Research acknowledges the significance of these partnerships, but their successful implementation is hampered by a variety of institutional and socioeconomic barriers, which lessens their impact on learner academic performance. This study examined how essential forming family-school partnerships are for enhancing the academic performance of Grade 10 learners in a rural public school in Limpopo, South Africa. The study aimed to better learner performance and provide support strategies to foster improvement. An interpretivism paradigm was adopted, employing semi-structured individual interviews and document analysis. Purposefully selected participants included four academically underperforming learners, their parents, and two teachers. The study was grounded in Epstein’s model of school, family, and community partnership, advocating for parental collaboration with school personnel through six key guidelines, promoting mutual responsibility among stakeholders. Findings revealed that parents understood the value of family-school partnerships and their roles within these. However, challenges such as other obligations, transportation issues, and time constraints were identified as hindrances preventing them from fully supporting their children’s academic integrity.